The natural history of dermatosparaxis Ehlers Danlos syndrome: an adult case series - Angwin, Chloe; Byers, P.; Dulfer, E.; Ghali, N.; Harris, Juliette; Haußer-Siller, Ingrid; McElroy, Abigail; Sobey, G.; van Dijk, F. S. (American journal of medical genetics, 2025)
Dermatosparaxis Ehlers Danlos syndrome (dEDS) is a very rare monogenic EDS that occurs due to biallelic pathogenic variants in ADAMTS2. Fifteen individuals with dEDS have been reported in the literature, with the oldest being 19 years at follow-up. Given the lack of information regarding adults with dEDS, our aim was to describe adults with dEDS to inform management recommendations in adulthood. We report five individuals (2:3 male:female) with an age range of 22-42 years. Complications include extreme skin fragility resulting in iatrogenic injury, redundant skin folds often requiring surgical resection, severe complications following a gastric volvulus secondary to a diaphragmatic hernia, and multiple fractures. Discussion of management considerations includes thorough investigations of acute pain, careful consideration of skin closure techniques and manual handling, as well as monitoring for reduced bone mineral density after low-impact fracture and/or post-menopause.